Multiparity upregulates placental plasminogen and urokinase-type plasminogen activator - Cortina, María Eugenia (2017)
Problem: Multiparity increased the number of trophoblast cells in decidua of both low and high fetal loss mouse models. However, they differ in fetal survival rate and maternal thymocyte subpopulations, suggesting that trophoblast invasiveness is not equivalent. Our aim was to explore the involved mechanism. Method of study: We studied placentae from primiparous and multiparous females of low and high fetal loss models. We investigated invasiveness in vitro, expression of plasminogen, and its activators: tissue type (tPA)‐urokinase type (uPA), and activity and expression of matrix metalloproteinases (MMP)‐2 and MMP‐9. Results: Placental invasiveness is upregulated by multiparity, but lesser in the high fetal loss model. Multiparous animals showed elevated expression of plasminogen and uPA. However, the high fetal loss combination showed higher expression of a short and less active fragment of uPA (LMW‐uPA). MMP‐2, MMP‐9, and tPA were unaffected. Conclusion: uPA would participate in the increased multiparity‐associated placental invasiveness.